Nitric Oxide Modulates Postharvest Physiology to Maintain Abelmoschus esculentus Quality Under Cold Storage - Xianjun Chen; Fenghuang Mo; Ying Long; Xiaofeng Liu; Yao Jiang; Jianwei Zhang; Cheng Zhong; Qin Yang; Huiying Liu (Horticulturae, 2025)
Cold storage is widely used for the postharvest preservation of fruits and vegetables; however, okra, as a tropical vegetable, is susceptible to chilling injury under low-temperature storage conditions, leading to quality deterioration, reduced nutritional value, and significant economic losses. Nitric oxide (NO), as an important signaling molecule, plays a crucial role in the postharvest preservation of fruits and vegetables. To investigate the effects of different concentrations of nitric oxide on the postharvest quality of okra under cold storage, fresh okra pods were treated with sodium nitroprusside (SNP), a commonly used NO donor, at concentrations of 0 (control), 0.5 (T1), 1.0 (T2), 1.5 (T3), and 2.0 mmol·L−1 (T4). The results showed that low-concentration NO treatment (T1) significantly reduced weight loss, improved texture attributes including hardness, springiness, chewiness, resilience, and cohesiveness, and suppressed the increase in adhesiveness. T1 treatment also effectively inhibited excessive accumulation of cellulose and lignin, thereby maintaining tissue palatability and structural integrity. Additionally, T1 significantly delayed chlorophyll degradation, preserved higher levels of soluble sugars and proteins, and enhanced the activities of key antioxidant enzymes, including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), contributing to improved oxidative stress resistance and membrane stability. In contrast, high-concentration NO treatments (T3 and T4) led to pronounced quality deterioration, characterized by accelerated membrane lipid peroxidation as evidenced by increased malondialdehyde (MDA) content and relative conductivity, and impaired antioxidant defense, resulting in rapid texture degradation, chlorophyll loss, nutrient depletion, and oxidative damage. These findings provide theoretical insights and practical guidance for the precise application of NO in extending shelf life and maintaining the postharvest quality of okra fruits.